Rapid microbiochemical identification of Corynebacterium diphtheriae and other medically important corynebacteria. - Thompson, J S (1983)
A rapid biochemical method based on the fermentation of carbohydrates, the hydrolysis of urea, and the reduction of nitrate was used to identify Corynebacterium diphtheriae, C. ulcerans, C. pseudodiphtheriticum, C. haemolyticum, C. pseudotuberculosis, C. pyogenes, C. ovis, the Centers for Disease Control JK group, and Rhodococcus (Corynebacterium) equi. With this procedure identification was confirmed for 133 stock cultures and clinical isolates of corynebacteria. Most were identified within 1 h and all were identified within 4 h after inoculation into the test substrates.